Interlocuções entre a cerâmica de Águeda Valentim e o barro das paneleiras de Goiabeiras: possibilidades para a construção artística dos alunos da rede estadual de Vitória (ES) - Eloiza Mara de Paula Rossoni (2017)
The present work provided the students of the state public network with artistic experiences based on pedagogical practices, through the study of the Paneleiras de Goiabeiras and the work of the ceramist Águeda Valentim. The clay was the basic material for artistic construction of the students and made possible the construction of knowledge and expressive development, besides offering opportunities in artistic and cultural environments. The process of artistic construction of the students was constituted of several elements derived from the experience and experience of the students with elements of the local culture and atelier of the ceramist. The insertion of the students between these two universes, besides contributing to the students' training process, and expanding the cultural repertoire, had as relevance of this research the interlocution between the cultural make of the Paneleiras de Goiabeiras and the artistic work of the ceramist Águeda Valentim, in the sense to promote the distinction between the two universes, without delegitimizing any. A book was elaborated with the experiences and possibilities of pedagogical activities that used the mud in the school scope. The theoretical approach of the work was supported by the authors Larossa (2005), Barbosa (2005), Sacomanni (2004), Dewey (2011) and other authors who dialogued with the approaches in the teaching-learning process.